2016
DOI: 10.1111/hepr.12718
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in‐hospital exercise on liver function, physical ability, and muscle mass during treatment of hepatoma in patients with chronic liver disease

Abstract: Aims: Sarcopenia and physical disability assessed by a 6-min walking test (6MWT) are associated with poor prognosis of patients with chronic liver disease (CLD). However, CLD patients with hepatocellular carcinoma (HCC) mostly rest in bed during hospitalization. We aimed to investigate the effects of therapeutic exercise on liver function, 6MWT, and skeletal muscle mass during HCC treatment in patients with CLD. Methods:We enrolled 54 CLD patients with HCC (median age, 76 years). During hospitalization, patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 45 publications
0
75
0
2
Order By: Relevance
“…Future studies of exercise and nutrition treatments on HCC and chronic liver disease are warranted since loss of skeletal muscle mass is the independent predictor of prognosis of HCC. In fact, there is some evidence showing that regular aerobic exercise decreased liver tumor development in a mice model [44], and branched-chain amino acid supplement was associated with less skeletal muscle atrophy in patients with HCC [45]. Besides, since most cases with HCC developed in patients with chronic liver disease, in which muscle volume loss and muscle strength decrease, we should evaluate the muscle mass and strength and treat with exercise and nutritional supplement not only in patients with chronic liver disease but also in those with HCC [45].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies of exercise and nutrition treatments on HCC and chronic liver disease are warranted since loss of skeletal muscle mass is the independent predictor of prognosis of HCC. In fact, there is some evidence showing that regular aerobic exercise decreased liver tumor development in a mice model [44], and branched-chain amino acid supplement was associated with less skeletal muscle atrophy in patients with HCC [45]. Besides, since most cases with HCC developed in patients with chronic liver disease, in which muscle volume loss and muscle strength decrease, we should evaluate the muscle mass and strength and treat with exercise and nutritional supplement not only in patients with chronic liver disease but also in those with HCC [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, its mechanisms remain unclear, and there is still more room for further research in the field of adipokines and how they affect HCC [40] and nutrition. Nutritional therapies [41] or exercise [42] may be useful as an adjunctive therapy for sarcopenia. However, there are a few reports on the efficacy of branched-chain amino acid granules [43, 44] and no reports on the efficacy of exercise in HCC patients treated with sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…Koya et al [30] demonstrated that therapeutic exercise improved cardiopulmonary function evaluated by a 6-min walking test in HCC patients.…”
Section: Discussionmentioning
confidence: 99%